2011
DOI: 10.1203/pdr.0b013e31821b1a92
|View full text |Cite
|
Sign up to set email alerts
|

Impact of N-Acetylcysteine on Neonatal Cardiomyocyte Ischemia-Reperfusion Injury

Abstract: ABSTRACT:Reactive oxygen species (ROS) are hypothesized to play a key role in myocardial ischemia-reperfusion (IR) injury after cardiopulmonary bypass in children. Clinical studies in adults and several animal models suggest that myocardial IR injury involves cardiomyocyte apoptosis and necrosis. This study investigated a potential relationship between IR-induced ROS production and neonatal cardiomyocyte apoptosis using both in vitro and ex vivo techniques. For in vitro experiments, embryonic rat cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…2 Instead, electron flow through the ETC upon reperfusion was described as a source of potentially detrimental reactive oxygen species (ROS), proposed to trigger ischaemia-reperfusion (I/R) injuries. 2 Conversely, the therapeutic use of untargeted antioxidants such as vitamin C for post-ischaemic cardioprotection has given contradictory results, [4][5][6][7][8][9] and itself produced detrimental side effects when therapeutically used. 10 These seemingly contradictory results were thought to be due to biphasic effects of ROS with high ROS concentrations leading to damage and lower concentrations eliciting adaptive responses.…”
Section: Introductionmentioning
confidence: 99%
“…2 Instead, electron flow through the ETC upon reperfusion was described as a source of potentially detrimental reactive oxygen species (ROS), proposed to trigger ischaemia-reperfusion (I/R) injuries. 2 Conversely, the therapeutic use of untargeted antioxidants such as vitamin C for post-ischaemic cardioprotection has given contradictory results, [4][5][6][7][8][9] and itself produced detrimental side effects when therapeutically used. 10 These seemingly contradictory results were thought to be due to biphasic effects of ROS with high ROS concentrations leading to damage and lower concentrations eliciting adaptive responses.…”
Section: Introductionmentioning
confidence: 99%
“…This cell line has been used extensively as a model for ischemia/reperfusion injury 2226 due to its high sensitivity to ischemia/reperfusion injury in terms of cell viability and mitochondrial respiration 24 . Moreover, H9c2 cells have been used in a number of studies involving CaMKII 2730 .…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2015) reported that cardiomyocyte apoptosis directly resulted in heart dysfunction during IR injury (Peng et al, 2011). Moreover, immature myocardium is more sensitive to oxidative stress (Umansky et al, 1995).…”
Section: Discussionmentioning
confidence: 99%